NAMITA GOKHALE: A CHAMPION OF INDIA'S LINGUISTIC AND CULTURAL DIVERSITY IN LITERATURE - Pareek, Dhanshree; Sharma, Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Namita Gokhale is well known for her literary work and for her service to the cause of Indian multilingualism and multiculturalism. Qualifying as an author, her writings explore gender, self, culture, and the post-modern world, rooted in India’s mythology and folk tales yet palpable in the urban reality of the new millennium. From comedy and satire to identifying the vulnerability of Indian society, she successfully blends humor and compassion and provides a voice for colloquial India. But writing was not the only thing that Gokhale contributed to society. She is the co-director of the Jaipur Literature Festival, making it an open stage vulnerable to the cultural and language marginalised. It has revolutionized literature and inspired conversation across cultures whilst truly promoting the multilingualism of India. Eliza Gokhale's work towards making literature more diverse means that she is a fighter between ‘mainstream’ and ‘regional’ literature. Her novels, such as Paro: Of the Cultural and Historical Consciousness, Dreams of Passion, and Shakuntala: The Play of Memory, are indicative of her conjugation with India. On the same note, it captures today's challenges, showing women’s strength and their search for an identity. Still connected with the past of Indian literature, Gokhale helps to define the development of contemporary Indian literature and remains the prominent voice for cultural changes.